ICT Equipment Application System (ICTEAS) / Roshidah Che Lah - Che Lah, Roshidah (2017)
Information and communication technology (ICT) equipment means desktop computers, laptops, servers, monitors, printers, audio-visual equipment, software and network equipment, but excludes IT consumables such as printer cartridges. The process of applying for ICT equipment for UiTM Kampus Kuala Terengganu rely on conventional methods such as using application forms, instant messaging and telephone call. The problems occurred when recording the information such as duplication of information, administration errors and data redundancy. Thus, ICT Equipment Application System (ICTEAS) has been developed by adapting theory of user experience. The project framework consist of six phases which are problem identification and planning, requirement gathering and analysis, design, development and implementation, project testing and evaluation and documentation and implemented Adapted Waterfall Model as system methodology. ICTEAS is being evaluated by three experts and 30 potential users. The evaluation construct is divided into six sections which are user interface, consistency, perceived usefulness, perceived ease of use, satisfaction and user experience. Result shows that the highest mean of the construct is user interface with 4.47 and standard deviation of 0.6288. In conclusion, the ICTEAS system is argued to contribute more benefits to the users and will help the users for better management and application for ICT equipment.